Option pricing, Zero Lower Bound, and COVID-19 - Giacomo Morelli; Lea Petrella (Risks, 2021)
This paper provides a quantitative assessment of equity options priced at the Zero Lower Bound, i.e., when interest rates are set essentially to zero. We obtain closed form formulas for American options when the Zero Lower Bound policy holds. We perform numerical implementation of American put options written on the stock Federal National Mortgage Association (FNMA) and of related bounds for the optimal exercise. The results show similarities with the corresponding European options priced at the Zero Lower Bound during the COVID-19 crisis.
Keywords: 330; COVID-19; option pricing; Zero Lower Bound